2019
DOI: 10.1103/physrevx.9.031046
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity near a Ferroelectric Quantum Critical Point in Ultralow-Density Dirac Materials

Abstract: The experimental observation of superconductivity in doped semimetals and semiconductors, where the Fermi energy is comparable to or smaller than the characteristic phonon frequencies, is not captured by the conventional theory. In this paper, we propose a mechanism for superconductivity in ultralow-density three-dimensional Dirac materials based on the proximity to a ferroelectric quantum critical point. We derive a low-energy theory that takes into account both the strong Coulomb interaction and the direct c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 66 publications
3
57
1
Order By: Relevance
“…In particular, doped topological materials are characterized by small electronic density and small density of states. As a result, the pairing interaction must be more singular [69]. Such an interaction is expected to be sensitive to the presence of disorder [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, doped topological materials are characterized by small electronic density and small density of states. As a result, the pairing interaction must be more singular [69]. Such an interaction is expected to be sensitive to the presence of disorder [75].…”
Section: Discussionmentioning
confidence: 99%
“…The action in Eq. (1) can be conveniently diagonalized in the manifestly covariant Bloch basis (MCBB), in which the electron spinor transforms as an ordinary SU(2) spin-1/2 [40,49,68,69]…”
Section: The Modelmentioning
confidence: 99%
“…For example, Raman scattering found that the hardening of the FE soft mode in the dilute metal is indistinguishably similar to what is seen in the insulator [21]. The anomaly in resistivity was found to terminate at a threshold carrier density (n * ), near which the superconducting transition temperature was enhanced [21] providing evidence for a link between superconducting pairing and ferroelectricity, a subject of present attention [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 98%
“…Before applying the BCS theory to further discuss the unusual 'high T c ' for Cu 0.09 Bi 2 Se 3 , we have examined if the adiabatic limit satisfies or not in Cu x Bi 2 Se 3 . The BCS solution is only a good description for the systems in the adiabatic limit [68,69], which requires the phonon energy ω must be much smaller than the carrier relaxation rate /τ , namely, ωτ 1. To make such an estimation, taking the highest phonon frequency A 2 1g mode 175.4 cm −1 at 3 K for Bi 2 Se 3 [70] and the scattering time τ = 5.2 × 10 −14 s for Cu 0.25 Bi 2 Se 3 [2], we obtain ωτ = 0.27 as an upper bound.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, according to our calculation of E F for Cu x Bi 2 Se 3 in the following, the Debye frequency (ω D ) [43] is actually comparable with the order of the E F , suggesting the antiadiabatic effect needs to be considered. If the optical phonons are at play in mediating superconductivity in Cu x Bi 2 Se 3 , the standard BCS theory has to be modified by including the antiadiabatic effect [68,71,72]. Theoretically, Wan and Savrasov showed the phonon dispersions of electron-doped Bi 2 Se 3 has an unusual large linewidth for both highest optical and acoustic phonons along Γ-Z direction [27].…”
Section: Discussionmentioning
confidence: 99%